The effect of assisted and resisted sprint training on acceleration and velocity in Division IA female soccer athletes - Upton, D. E. (The Journal of Strength and Conditioning Research, 2011)
This investigation evaluated the effects of a 4-week, 12-session training program using resisted sprint training (RST), assisted sprint training (AST), and traditional sprint training (TST) on maximal velocity and acceleration in National Collegiate Athletic Association (NCAA) Division IA female soccer athletes (n = 27). The subjects, using their respective training modality, completed 10 maximal effort sprints of 20 yd (18.3 m) followed by a 20-yd (18.3 m) deceleration to jog. Repeated measures multivariate analyses of variance and analyses of variance demonstrated significant (p < 0.001) 3-way interactions (time × distance × group) and 2-way interactions (time × group), respectively, for both velocity and acceleration. Paired t-tests demonstrated that maximum 40-yd (36.6-m) velocity increased significantly in both the AST (p < 0.001) and RST (p < 0.05) groups, with no change in the TST group. Five-yard (4.6-m), 15-yd (13.7 m), 5- to 15-yd (4.6- to 13.7-m) acceleration increased significantly (p < 0.01) in the AST group and did not change in the RST and TST groups. Fifteen- to 25-yd (13.7- to 22.9-m) acceleration increased significantly (p < 0.01) in the RST group, decreased significantly (p < 0.01) in the AST group, and was unchanged in the TST group. Twenty-five to 40-yd (22.9- to 36.6-m) acceleration increased significantly (p < 0.05) in the RST group and remained unchanged in the AST and TST groups. It is purposed that the increased 5-yd (4.6-m) and 15-yd (13.7-m) accelerations were the result of enhanced neuromuscular facilitation in response to the 12-session supramaximal training protocol. Accordingly, it is suggested that athletes participating in short distance acceleration events (i.e., <=15 yd; <=13.7 m) use AST protocols, whereas athletes participating in events that require greater maximum velocity (i.e., >15 yd; > 13.7 m) should use resisted sprint training protocols.